The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1042/bsr20200669
|View full text |Cite
|
Sign up to set email alerts
|

Carboxypeptidase A4 promotes cardiomyocyte hypertrophy through activating PI3K-AKT-mTOR signaling

Abstract: Carboxypeptidase A4 (CPA4) is a member of the metallocarboxypeptidase family. Current studies have identified the roles of CPA4 in cancer biology and insulin sensitivity. However, the roles of CPA4 in other diseases are not known. In the present study, we investigated the roles of CPA4 in cardiac hypertrophy. The expression of CPA4 was significantly increased in the hypertrophic heart tissues of human patients and isoproterenol (ISO)-induced hypertrophic heart tissues of mice. We next knocked down Cpa4 with sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…CPA4 expression inhibited the tumor proliferation and regulated the expression of stem cell characteristics in hepatocellular carcinoma ( 22 ). Nevertheless, CPA4 was found to be a key regulator of cardiac hypertrophy through activating PI3K-AKT-mTOR signaling and may serve as a promising therapy target for hypertrophic cardiac diseases ( 23 ). CPA6 could promote cell proliferation and migration through regulating the AKT signaling pathway in hepatocellular carcinoma ( 24 ).…”
Section: Discussionmentioning
confidence: 99%
“…CPA4 expression inhibited the tumor proliferation and regulated the expression of stem cell characteristics in hepatocellular carcinoma ( 22 ). Nevertheless, CPA4 was found to be a key regulator of cardiac hypertrophy through activating PI3K-AKT-mTOR signaling and may serve as a promising therapy target for hypertrophic cardiac diseases ( 23 ). CPA6 could promote cell proliferation and migration through regulating the AKT signaling pathway in hepatocellular carcinoma ( 24 ).…”
Section: Discussionmentioning
confidence: 99%
“…Existing reports indicate that histone modification and DNA methylation are involved in the occurrence and development of myocardial hypertrophy ( 37 , 38 ). The occurrence and development of cardiac hypertrophy is also accompanied by the abnormal activation of a large number of important signaling pathways ( 5 , 39 , 40 ). Consequently, there is an increased level of interest in how key signaling pathways participate in the epigenetic regulation of cardiac hypertrophy ( 41 , 42 ).…”
Section: Discussionmentioning
confidence: 99%
“…In our previous study, it was shown that the imbalance in the modification of histone H3K9ac, a process mediated by histone acetylases (HATs), is involved in phenylephrine (PE)-induced cardiomyocyte hypertrophy ( 4 ). Several studies have shown that cardiac hypertrophy can be induced by the activation of multiple signaling pathways ( 5 8 ). The extracellular signal-regulated protein kinase (ERK) signaling pathway is considered to play a particularly important role in regulating pathological cardiac hypertrophy ( 9 11 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, the multi-target characteristics of TCM monomers suggest that PU has multiple therapeutic targets (37). Numerous signaling pathways are associated with the pathophysiology of MH, including the 5'AMP-activated protein kinase/mTOR (38), PI3K/AKT/mTOR (39) and insulin-like growth factor 1/PI3K/AKT (40) signaling pathways. Therefore, the exploration of the mechanism of PU on MH to achieve the effect of precise treatment is urgent.…”
Section: Introductionmentioning
confidence: 99%